The Relationship between Birth Weight and Neonatal Sepsis Incidence: Literature Review - Zambri, Haniah; Fetriyah, Umi Hanik; Nito, Paul Joae Brett (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2021)
Neonatal sepsis contributes as much as 75% in increasing the neonatal mortality rate that occurs first week of birth. Neonatal sepsis is characterized by entry of bacteria in the blood that can be life-threatening. Process of neonatal sepsis can occur very quickly, if not treated with adequate treatment, death can occur within 24-48 hours. Neonatal sepsis is affected by infant factors like low birth weight (LBW). LBW in neonates can be easily infected due to immature immune formation. The study used literature review methods. Literature sourced from five databases: Biomed Central, Plus One, Pubmed, Proquest and Science Direct. Search with PICOS framework 15 journals used to analyze and obtained. Results showed the incidence of neonatal sepsis with the percentage incidence of sepsis at 16.9%-77.8%. LBW is risk of developing sepsis with the highest percentage compared to other birth weight classifications. Majority of journals stated there was a significant relationship between birth weight and neonatal sepsis (p value: 0,0131-0,001). Nurses play a role in conducting assessment begin ranging from pregnant to the birth and give a comprehensive nursing care earlier for birth babies less than 2.500 gram. It's effort decrease incidence of neonatal sepsis.